PENGARUH LIFESTYLE, PROMOSI ONLINE, HARGA TERHADAP MINAT BELI PADA THRIFT TRISULA RATU - Oka Astana, I Gusti Made; Pebriani, Komang Nita (Jurnal Daya Saing, 2025)
This study aims to analyze influence of lifestyle, online promotion, and price on consumer purchase intention at Thrift Trisula Ratu in Singaraja City. The background of this research is based on the growing trend of thrifting among the younger generation, who prioritize stylish appearance while considering economic and sustainability aspects.however, Thrift Trisula Ratu has experienced fluctuating sales, which are suspected to be influenced by suboptimal promotional strategies, pricing adjustments, and shifts in consumer lifestyle. This research uses a quantitative approach with purposive sampling technique involving 75 respondents who have shopped at the store. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 30. The results show that lifestyle, online promotion, and price simultaneously have a significant effect on purchase intention. Partially, each of the three variables also has a positive and significant effect, with lifestyle emerging as the most dominant factor influencing purchase intention. These findings imply that to increase consumer interest, the store, must adapt its marketing strategies to align with the target market’s lifestyle, optimize digital promotion, and offer competitive pricing